Inclusion of CIDR in ovsynch protocol to improve fertility in postpartum subestrus buffaloes - RAVIKUMAR, K; ASOKAN, S A; VEERAPANDIAN, C (The Indian Journal of Animal Reproduction, 2023)
Twenty four postpartum subcstrus buffaloes nol showing observed estrus within 60 days after calving wererandomly and equally divided into ovsynch-subcstrus and ovsynch plus CIDR-subcstrus groups. Ovsynch-subcstrus groupbuffaloes were subjected to ovsynch protocol which consisted of 100 μg i.m. injection of GnRH on the day of start ofsynchronization (d 0), 25 mg i.m. injection of PGF2a seven day£ laur (d. 7), another 100 μg i m iojecrioo of GnRH 48 hafter PGF,a (d 9) and timed insemination 16 to 18 h after second GnRH injection (d 10). Ovsynch plus CIDR-subcstrusbuffaloes ;.,ere subjected to ovsynch plus CIDR protocol which included intra vaginal placement of CIDR device for a periodof 7 days starting from first GnRH injection (d 0) to PGF2a injection (d 7) for synchronization of ovulation. Blood sampleswere collected from all experimental animals on d -10 and d O ,d 7, and d 9 days after insemination for the estimation ofprogesterone. During the treatment protocol none of the buffaloes exhibited visible premature estrus signs. Howeverprogesterone estimation showed that 25 per cent had exhibited premature estrus. The estrus detection rates were 41.66 and58 .33 per cent in ovsynch-subestrus and ovsynch plus CIDR-subestrus respectively. Most buffaloes showed intcrmcdialesigns of estrus. The ovulatory response and first service conception rates were 83.33 and 33.33 and 100 and 41.66 per centin ovsynch-subestrus and ovsynch plus CIDR-subestrus groups respectively.
Keywords: Ovsynch; CIDR; subcslrus buffaloes; fertility